KAJIAN FIKIH KONTEMPORER: SEBUAH REKONSTRUKSI AWAL - Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2017)
Principally, any knowledge which is systematically codified and communicated either in oral and written form has philosophical basis. The basic assumption of a scientist which is followed by scientific steps of research such as using correct approach, employing theoretical framework, checking appropriate validity of information, finding the relationship between subject and object is central to the structure of knowledge including science, humanity, social, and religion. As such, knowledge has certain structure by which it opens to further investigation and development. Kata kunci: Kajian Fikih Kontemporer, Metode, Pendekatan